Abdominal paracentesis: use of a standardised procedure checklist and equipment kit improves procedural quality and reduces complications. Issue 5 (2nd May 2018) - Fyson, Jeremy; Chapman, Laura; Tatton, Michael; Raos, Zoë
ABSTRACT: Background: Paracentesis is a common invasive procedure performed by junior doctors. Audit of procedure conduct at two New Zealand hospitals in 2012 revealed poor performance across a range of quality measures, including documentation of informed consent, excessive catheter dwell times and inappropriate albumin prescription. Complication rates were 12.7%, compared with published rates of around 9%. A local procedure protocol did not exist. Aim: To evaluate the effect of a standardised procedure checklist (PC) and equipment kit (EK) on procedural quality and complication rates for abdominal paracentesis. Methods: After presenting the 2012 audit results to resident doctors, we reviewed the paracentesis literature and developed a local procedure protocol (PC and EK). These tools were made readily available after an education campaign. Paracenteses performed after the intervention were studied to determine the impact on procedural quality and safety. Results: Seventy‐four paracenteses (14 diagnostic; 60 therapeutic) were performed in 10 months after the introduction of PC and EK. Significant improvements were observed with the use of PC including documentation of informed consent (97% vs 74%, P = <0.01) and aseptic technique (100% vs 62%, P = <0.01). Catheter dwell times <6 h improved (72% vs 48%, P = 0.02). Inappropriate albumin prescriptions were less frequent (21% vs 66%, P = <0.01). Complication rates decreased from 12.7% to 2.8% ( P = <0.01). Conclusions: The PC and EK improved rates of informed consent, appropriate documentation and protocol adherence. Significantly fewer procedure‐related complications occurred after introduction of these tools.